2010
DOI: 10.1590/s0100-06832010000400034
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos do solo influenciados por sucessivas aplicações de dejetos suínos em áreas agrícolas de Santa Catarina

Abstract: RESUMO(1) Recebido para publicação em setembro de 2009 e aprovado em maio de 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
1
45

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 15 publications
9
68
1
45
Order By: Relevance
“…Organic matter was not significantly altered by the treatments (Figure 2a), a result similar to that observed by Muraishi et al (2011) andScherer et al (2010). However, Lourenzi et al (2011) found different results, with increasing organic matter in deeper soil layers after pig slurry application.…”
Section: Soil Chemical Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…Organic matter was not significantly altered by the treatments (Figure 2a), a result similar to that observed by Muraishi et al (2011) andScherer et al (2010). However, Lourenzi et al (2011) found different results, with increasing organic matter in deeper soil layers after pig slurry application.…”
Section: Soil Chemical Propertiessupporting
confidence: 88%
“…However, in lower layers (0.025-0.40 m) exchangeable K increased with an increasing application rate of pig slurry, and this is somewhat at odds with results found by Scherer et al (2010) in a Cambisol and in an Inceptisol soil in the west of Santa Catarina, Brazil; it is also at odds with results reported by Queiroz et al (2004) in a Ultisol soil in Rio Grande do Sul, Brazil, where exchangeable K was found to accumulate in the upper soil layers and to decrease in deeper layers after pig slurry application.…”
Section: Soil Chemical Propertiesmentioning
confidence: 57%
“…There are several reports in the literature of increased levels of soil nutrients after pig slurry application under field conditions (Ceretta et al, 2003;Scherer et al, 2010;Girotto et al, 2010;Veiga et al, 2012). However, these studies used organic fertilizers with a higher dry matter content compared with the biofertilizer used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…According to these authors, there was no increase in soil pH, and K and organic C after applying the organic fertilizer. Scherer et al (2010) found that in areas treated with swine waste in the long term (around 15 years, and between 20 and 25 years), the P, K, Cu and Zn concentrations increased markedly in the soil surface layers, especially in 0-0.05 m. Girotto et al (2010) found linear increases in available Cu and Zn concentrations in soil layers of a no-tillage area treated with 17 applications of up to 80 m 3 ha -1 of pig slurry over 78 months. According to the authors, the levels of available Cu and Zn in the 0-0.10 m soil layer of the treatment with the highest rate of organic fertilizer were, on average, 12 and 24 times higher, respectively, than in the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation